EFFECT OF WELDING SEQUENCE ON DISTORTION RESULTS IN BRACKET CONNECTIONS - Suheri, Suheri; Widodo, Syamsul Bahri; Arif, Zainal; Surawan, Surawan; Ali, Sulaiman; Pamungkas, Nurman; Syafii, Muhamad (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2024)
The distortion in the shape of the weld specimen is influenced by the uneven heat distribution during the welding process. There is also distortion in the welding modeling performed on the bracket joint. The modeling scenario of the bracket joint forms the basis for measuring the distortion results. Therefore, when we model the bracket joint, we obtain varying distortion results. There are three lines to observe the distortion effects. Lines a, b, and c are located on the X and Y axes (center), while line c is on the X and Y axes (+). Line a is on the X and Y axes (-). The test specimen that has been modeled is the result of numerical modeling, which is then used to calculate the magnitude of the distortion on the longitudinally stiffened plate test specimen. For the numerical modeling of the bracket joint, the result of scenario 1 is distortion. Meanwhile, the distortion results of the bracket joint modeling in scenarios 1 and 2 show that the distortion value obtained in scenario 2 is higher than that obtained in scenario 1. This is influenced by the order of welding lines used in the bracket joint modeling.